2001
DOI: 10.1007/bf02345151
|View full text |Cite
|
Sign up to set email alerts
|

Propagation velocity measurement: Autocorrelation technique applied to the electromyogram

Abstract: Muscle fibre conduction velocity is an important measurement in electrophysiology, both in the research laboratory and in clinical practice. It is usually measured by placing electrodes spaced at known distances and estimating the transit time of the action potential. The problem, common to all methods, is the estimation of this time delay. Several measurement procedures, in the time and frequency domains, have been proposed. Time-domain strategies usually require two acquisition channels, whereas some frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The presence of dips in the power spectrum of surface EMG signals detected by a bipolar electrode system has a counterpart in the temporal domain, that is in the autocorrelation function of the signal, indeed, it can be shown that the first dip introduced by a bipolar recording in the power spectrum approximately corresponds to the first minimum of the autocorrelation function of the signal (SPINELLI et al, 2001). SPINELLI et al (2001) proposed this method for estimating CV from invasive recordings, although the technique may fit surface recordings better.…”
Section: Autocorrelation Techniquementioning
confidence: 97%
See 2 more Smart Citations
“…The presence of dips in the power spectrum of surface EMG signals detected by a bipolar electrode system has a counterpart in the temporal domain, that is in the autocorrelation function of the signal, indeed, it can be shown that the first dip introduced by a bipolar recording in the power spectrum approximately corresponds to the first minimum of the autocorrelation function of the signal (SPINELLI et al, 2001). SPINELLI et al (2001) proposed this method for estimating CV from invasive recordings, although the technique may fit surface recordings better.…”
Section: Autocorrelation Techniquementioning
confidence: 97%
“…SPINELLI et al (2001) proposed this method for estimating CV from invasive recordings, although the technique may fit surface recordings better. The method has the same problems related to the detection of spectral dips.…”
Section: Autocorrelation Techniquementioning
confidence: 98%
See 1 more Smart Citation
“…The surface electromyogram (EMG) is a rather ubiquitous tool used, for example, as a measure of muscular effort in traumatology, as an evaluation parameter in rehabilitation engineering, as the control input to myoelectric prostheses and as another diagnostic piece of information in myopathies many times faced in clinical medicine [1,2]. It can also be used to estimate the muscle action potential propagation velocity [3]. Its analysis permits a better knowledge of the muscle acti-vation sequence, either in lower or upper extremities, during predetermined voluntary movements.…”
Section: Introductionmentioning
confidence: 99%
“…Nestes casos, as razões da proposição de tais técnicas eram, principalmente, o problema do uso de eletrodos monopolares ou bipolares para estimação da CV. Spinelli et al (2001) também abordam esta questão, porém, propondo um método baseado em autocorrelação. Solomonow et al (1990) (Solomonow et al, 1990).…”
Section: -Relações Entre Os Indicadores De Fadiga E Fatores Que Os Inunclassified